Synthesis of a new heterocyclic system [1,3]oxazolo[4,5-c][1,5,2]oxazaphosphepin - Brusnakov, M.Y.; Shyshatska, Y.O.; Golovchenko, O.V.; Броварець, В.С.; Potikha L.М. (Reports of the National Academy of Sciences of Ukraine, 2022)
This paper is devoted to the study of the properties of diethyl esters of 2-aryl-1,3-oxazol-4-ylphosphonic acids, which contain a (2-hydroxyethyl)(R)amino group in the adjacent 5th position of the oxazole ring, useful for further structural transformations. Acylation of diethyl 5-[(2-hydroxyethyl)](R)amino-2-aryl-1,3-oxazol- 4-ylphosphonates with mesyl chloride in tetrahydrofuran in the presence of triethylamine gave 2-[2-aryl- 4-(diethoxyphosphoryl)-1,3-oxazol-5-yl](R)aminoethyl methanesulfonates. N-methyl substituted methanesulfonates are converted into intramolecular cyclization products upon heating with triethylamine in acetonitrile — 7-aryl-1-ethoxy-5-methyl-1,3,4,5-tetrahydro-1λ5-[1,3]oxazolo[4,5-c][1,5,2]oxazaphosphepin-1-ones, which are derivatives of the new heterocyclic system. Derivatives of [1,3]oxazolo[4,5-c][1,5,2]oxazaphosphepine are representatives of the new heterocyclic system. The structure of the new compounds was proved by data of elemental analysis, mass spectrometry and data of IR spectra and 1H, 13C, 31P NMR spectra.